Description of The Characteristics of Hypertension in The Elderly Posyandu And Pusling The Jailolo PKM Work Area in July 2023 - Safwan Pratama S. Bachmid (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to determine the characteristics of hypertension sufferers at the Elderly Posyandu and Pusling in the Jailolo Community Health Extension work area in July 2023. The research method used was descriptive observational research with 20 respondents. The results of the study showed that the level of knowledge of respondents about hypertension in the elderly at the Jailolo Health Center was included in the category of sufficient knowledge, the attitudes of respondents about hypertension in the elderly at the Jailolo Health Center were mostly included in the category of sufficient and lacking and the behavior of respondents about hypertension in the elderly at the Jailolo Health Center was mostly included in the category of lacking. It can be concluded that in general public knowledge can be said to be sufficient, but community behavior that causes hypertension is still carried out such as salt consumption which is included in the high category and smoking habits.